PENGARUH CITRA PERUSAHAAN, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Penumpang New Atlas Taksi Semarang) - Miranthi, Andra; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2017)
As time goes by, transportation becomes one of the main needs to support activity. The development of taxi services continues occur in various major cities, especially Semarang. This is indicated by the increasing company that doing those business. The purpose of this study is to know the influence of corporate image, service quality, and price perceptions on the repurchase intention of New Atlas Taxi Semarang, with customer satisfaction as intervening variable.Purposive sampling method is used for this research, samples were collected from 100 respondents (consumerwho has been using New Atlas Taksi service within the last 1 year). Multiple regression analysis is used for this study.The results show that company image, service quality, and price perception have a positive and significant effect on customer satisfaction. Service quality has the highest influence on customer satisfaction. Then, company image, service quality, price perception, and customer satisfaction have a positive and significant effect on repurchase intention. Service quality has the highest influence on repurchase intention